University Digital Engagement of Students - Maria C. Pereira; Ferreira, J.; Moro, S.; Gonçalves, F. (Sense, Feel, Design. INTERACT 2021. Lecture Notes in Computer Science, 2022)
Most of the prospective university students, especially from abroad, search on the online social networks what other students, present and former, are saying about the universities and the programs. Students express their sentiments regarding universities, programs, and courses they attended, or they are attending, in informal conversations on online social networks. We aim to understand how universities’ and programs’ enrolment numbers, relate to students’ sentiments expressed on online social networks, and how this electronic word of mouth relates to the dissemination of information about the universities and the programs on online social networks. The research goal of this study is to test an approach to engage with students on online social networks and measure the impact of this interaction by analyzing the feedback from former and present students, and the enrolment numbers of new students.